2014
DOI: 10.1089/bfm.2014.0011
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Stage-Related Expression of Sialylated and Fucosylated Glycotopes of Human Milk α-1-Acid Glycoprotein

Abstract: Background: Because terminal sugars of a-1-acid glycoprotein (AGP) are reported to be involved in antiinflammatory and immunomodulatory processes, their expressions might have an influence on the proper function of immune system of newborns. Here, relative amounts of sialylated and fucosylated glycotopes on human milk AGP over normal lactation were investigated. Materials and Methods: AGP concentration and relative amounts of its sialylated and fucosylated glycovariants were analyzed in early colostrum, colost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Although according to Froehlich et al [21] there is no common pattern for glycosylation of milk glycoproteins over lactation, the sialylation and fucosylation changes are more or less similar to those of other milk glycoproteins, human milk oligosaccharides (HMOs), and those of the entire N-glycan repertoire of whey proteins from human milk [25]. The decrease of α2,6-sialylation (SNA-reactive) observed by us, with relatively stable α2,3-sialylation (MAA-reactive) over lactation, was found to be similar to that described recently for human milk AGP [26] and HMOs [27]. Also, the expression of sialylated and In Table 1 values are given as the mean ± SD and median and 25th-75th percentile in parentheses.…”
Section: Discussionsupporting
confidence: 87%
“…Although according to Froehlich et al [21] there is no common pattern for glycosylation of milk glycoproteins over lactation, the sialylation and fucosylation changes are more or less similar to those of other milk glycoproteins, human milk oligosaccharides (HMOs), and those of the entire N-glycan repertoire of whey proteins from human milk [25]. The decrease of α2,6-sialylation (SNA-reactive) observed by us, with relatively stable α2,3-sialylation (MAA-reactive) over lactation, was found to be similar to that described recently for human milk AGP [26] and HMOs [27]. Also, the expression of sialylated and In Table 1 values are given as the mean ± SD and median and 25th-75th percentile in parentheses.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, as suggested by Newburg, 2 some human milk oligosaccharides (HMOs) may provide a background for construction of innovative therapeutics as well as prophylactic bioagents given for neonates during the postnatal period, particularly those delivered preterm in unfavorable and detrimental conditions. So far the free HMOs, 1 human milk N-glycome, 5 and glycan profiles of N-and/or O-glycans of some glycoproteins, 6 such as lactoferrin, 7 bile salt-stimulated lipase, 8 secretory immunoglobulin A, 9,10 a-1-acid glycoprotein (AGP), 11 and fibronectin, 12 have been characterized in detail. Over the process of lactation, within milk maturation, the degree and type of sialylation and fucosylation of milk glycoproteins change and partly overlap with observed trends for HMOs abundantly present in milk.…”
Section: Introductionmentioning
confidence: 99%
“…Over the process of lactation, within milk maturation, the degree and type of sialylation and fucosylation of milk glycoproteins change and partly overlap with observed trends for HMOs abundantly present in milk. 6,11,12 Gao et al 13 have suggested that alteration in glycan structures during lactation goes hand in hand with a transformation in defense mechanisms that occur from newborns to young infants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations